Psychological and Social Impact of Recurrent Aphthous Ulcers among Young Adults (Academia Journal of Medicine, 2026)
Background: Recurrent aphthous ulcers are painful sores that appear in the mouth and  can make it hard to eat, talk, be social, and feel good about yourself. Young adults are  affected by this condition due to multifactorial reasons. Hence, the current study was  undertaken to investigate the psychological and social effects of recurring aphthous ulcers  in young adults and to examine their correlation with clinical ulcer-related parameters.  Materials and Methods: A cross-sectional study was conducted involving 150 young  individuals with recurrent aphthous ulcers. Demographic information, ulcer type, ulcer  frequency, number of ulcers, pain score, episode duration, and functional impairments were  documented. Structured scores were used to measure the psychological and social effects.  Results: A moderate-to-high psychosocial impact was observed in 88 participants (58.7%).  There was no significant link between age, gender, and psychosocial impact. Frequent ulcer  episodes, many ulcers, elevated pain scores, prolonged duration, challenges in eating and  speaking, and avoidance of social interaction were substantially correlated with increased  psychosocial impact. Psychological and social evaluations increased considerably with  ulcer severity. Conclusion: Recurrent aphthous ulcers adversely impacted the psychological  and social well-being of young people, particularly when the ulcers were numerous, painful,  or severe.
Keywords: Recurrent aphthous ulcers; young adults; psychological impact; social impact; oral health-related quality of life; stress.